Effectiveness Of Implementing The Family Hope Program On The Welfare Of Poor Families In East Belitung District - Arief Wibowo Basrie; Rina Hermawati; Eddy Nurmanto (LPPM Universitas PGRI Sumatera Barat, 2024)
The government's program to improve community social welfare is through the Family Hope Program, with the aim of reducing the burden of expenditure, increasing access to health services, education and social empowerment, and playing a role in breaking the chain of poverty between generations. It is necessary to know the variables and indicators that influence the effectiveness of the family hope program on the welfare of poor families in East Belitung Regency, as a reference in planning future activities. The research method is a quantitative method, using Inferential Statistics - Structural Equation Model. The number of respondents was 341 people, namely individuals from beneficiary families of the Family Hope Program. The data collection technique was carried out using the Cluster Random Sampling method, through an Interview Survey. The research instrument is a questionnaire list of written questions, while the questionnaire is prepared in ordinal form on a Likert scale. The research results show that there is a positive and significant relationship, where Recipient Data, Distribution of Social Assistance, and Social Assistance Services influence the Welfare of Poor Families, while the research results show that there is no positive and significant relationship between Assistance and the Welfare of Poor Families. Based on the results of the R Square test, 51.5% of the welfare of poor families is influenced by the significance of the Recipient Data Variable, Distribution of Social Assistance, and Social Assistance Services (Hypothesis test results), while 48.5% is influenced by other factors, including basic services in the field of education and health, payment of BPJS Health contributions by local governments, health services for the disabled and the elderly, and home repairs through the livable housing program.